1996
DOI: 10.1073/pnas.93.24.13754
|View full text |Cite
|
Sign up to set email alerts
|

Metal binding properties and secondary structure of the zinc-binding domain of Nup475

Abstract: Nup475 is a nuclear zinc-binding protein of unknown function that is induced in mammalian cells by growth factor mitogens. For structural studies by nuclear magnetic resonance spectroscopy, we used a more soluble two-domain peptide that had a single amino acid substitution in a nonconserved amino acid residue in the second Cys 3 His repeat. The mutant peptide unexpectedly showed loss of one of its metal binding sites and displayed ordered structure for only the first Cys 3 His sequence. On the basis of the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
128
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 36 publications
3
128
0
Order By: Relevance
“…Such studies have been difficult in the past because of problems with solubility of the recombinant protein and its constituent peptides. Recent studies using a peptide from the mouse TTP tandem zinc finger domain, in which a tyrosine-tolysine mutation had been created at position 143 of the mouse protein (GenBank accession number NP_035886), suggested that whereas a structure could be determined for the first zinc finger by NMR methods, a structure could not be solved for the second zinc finger (26,27). Similarly, in the present studies, the amino acids composing the first zinc finger of the purified recombinant human TTP (102-174) peptide could be assigned, but those of the second zinc finger could not be identified, perhaps because of similar problems to those observed by Berg et al (27) with the mutant mouse peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have been difficult in the past because of problems with solubility of the recombinant protein and its constituent peptides. Recent studies using a peptide from the mouse TTP tandem zinc finger domain, in which a tyrosine-tolysine mutation had been created at position 143 of the mouse protein (GenBank accession number NP_035886), suggested that whereas a structure could be determined for the first zinc finger by NMR methods, a structure could not be solved for the second zinc finger (26,27). Similarly, in the present studies, the amino acids composing the first zinc finger of the purified recombinant human TTP (102-174) peptide could be assigned, but those of the second zinc finger could not be identified, perhaps because of similar problems to those observed by Berg et al (27) with the mutant mouse peptide.…”
Section: Discussionmentioning
confidence: 99%
“…TTP fusion protein and its tandem zinc finger peptide each bind zinc with an affinity similar to those of other wellcharacterized zinc finger peptides (17)(18)(19). Zinc binding is required for the TNF mRNA ARE binding activity of TTP (9).…”
mentioning
confidence: 99%
“…Metal binding by His residues involves donating imidazole nitrogen lone-pair electrons to the unfilled orbitals of the metal, and cysteines can substitute for His in this process. 38,[41][42][43] Thus, mutants His267Cys, His272Cys, and His267Cys/His272Cys were created. The imidazole proton of His has a pK a of 6.6 and can mediate pH-dependent effects in proteins.…”
Section: Conserved Histidine Pair In Tm6mentioning
confidence: 99%